Activation of the JAK/STAT pathway in Behcet's disease - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (NATURE PUBLISHING GROUP, 2015)
Th1/Th17-type T-cell responses are upregulated in Behcet's disease (BD). However, signaling pathways associated with this aberrant immune response are not clarified. Whole-genome microarray profiling was performed with human U133 (Plus 2.0) chips using messenger RNA of isolated CD14(+) monocytes and CD4(+) T cells from peripheral blood mononucleated cell (PBMC) in patients with BD (n = 9) and healthy controls (HCs) (n = 9). Flow cytometric analysis of unstimulated (US) and stimulated (phytohaemagglutinin) signal transducer and activator of transcription (STAT3) and pSTAT3 expressions of PBMCs were also analyzed (BD and HC, both n = 26). Janus family of kinase (JAK1) was observed to be upregulated in both CD14(+) monocytes (1.95-fold) and CD4(+) T lymphocytes (1.40-fold) of BD patients. Using canonical pathway enrichment analysis, JAK/STAT signaling was identified as activated in both CD14(+) monocytes (P = 9.55E - 03) and in CD4(+) lymphocytes (P = 8.13E - 04) in BD. Interferon signaling was also prominent among upregulated genes in CD14(+) monocytes (P = 5.62E -05). Glucocorticoid receptor signaling and interleukin (IL-6) signaling were among the most enriched pathways in differentially expressed genes in CD14(+) monocytes (P = 2.45E - 09 and 1.00E - 06, respectively). Basal US total STAT3 expression was significantly higher in BD (1.2 vs 3.45, P < 0.05). The JAK1/STAT3 signaling pathway is activated in BD, possibly through the activation of Th1/Th17-type cytokines such as IL-2, interferon (IFN-gamma), IL-6, IL-17 and IL-23.
Keywords: REGULATORY T-CELLS; SIGNALING PATHWAY; GENETIC-VARIANTS; HAN CHINESE; TH1 CELLS; SUSCEPTIBILITY; TRANSCRIPTION; ASSOCIATION; INVOLVEMENT; MECHANISMS